Creativity Book Project as A Strategy for Developing Early Childhood Reading Literacy through Parenting Activities - Nanik Rahayu; Septiyani Endang Yunitasari (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research aims to explain the impacts and benefits of developing creativity books as a strategy for enhancing early childhood literacy, involving the role of parents in the learning process. Books are essential sources of information for children, and parents and teachers can provide literacy stimulation through engaging books. Involving students in creating creativity books and including parents in every step is a meaningful experience for children. The project aims to enhance children's creativity, provide an understanding of the benefits of books, and strengthen cooperation with parents in supporting children's literacy. This research employs a qualitative approach with a case study at the Early Childhood Education School, TK Widya Kusuma Sari Denpasar, through observation, structured interviews, and documentation studies. The results include several creative books students produced collaborating with parents in parenting activities. This study highlights the importance of developing early childhood literacy through creativity book projects. It emphasizes the role of parents in enhancing the quality of children's learning at home and school.